Comparison of splinting, splinting plus local steroid injection and surgery in carpal tunnel syndrome treatment [Karpal Tünel Sendromu Tedavisinde Splint, Splint ile Lokal Steroid Enjeksiyonu ve Cerrahinin Karşilaştirilmasi] - (:unkn) unknown (My University, 2006)
Objective: This study was designed to compare the short term efficacy of splinting, splinting plus local steroid injection and surgery in mild or moderate idiopathic carpal tunnel syndrome (CTS) treatment. Materials and Methods: Fifty-seven hands were divided into three groups in which 23 hands were splinted, 23 hands were splinted and one time steroid injection was applied, and 11 hands were operated. The patients were evaluated before and 90 days after treatment with electrophysiological studies and Boston Questionnaire (BQ). Results: In BQ symptom severity (SS) and functional capacity (FC) scores, median motor nerve distal latency, median motor nerve compound muscle action potential amplitude at wrist, and ankle, median sensorial nerve velocity at 2nd digit-wrist segment, and median sensorial nerve action potential amplitude at 2nd digit-wrist segment measures statistically significant improvements were found in both of three methods (p<0.05). None of the treatment methods was found superior (p>0.05). However the SS score of splinting and splinting plus injection were statistically lower than surgery at 90th day and the FC score of splinting plus injection was lower than splinting and surgery. In median sensorial nerve velocity at palm-wrist segment all treatments were increased the velocity (p<0.05), but surgery was found as superior than the others (p<0.05). In two hands of surgery group complications were observed, which one of them was painful scar formation and the other was complex regional pain syndrome. There were no complications in conservative treatment groups. Conclusion: Conservative treatments provide comparable recovery to surgery in short term. Splinting alone is an effective method for reducing the symptoms and local steroid injection together with splinting improve functional healing.
Keywords: Carpal tunnel syndrome; Local steroid injection; Splinting; Surgery